1997
DOI: 10.1097/00005053-199708000-00005
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Symptoms Associated with Early and Late Onset Alcohol Dependence

Abstract: This study was designed to determine whether the prevalences of the DSM-III alcohol abuse/dependence symptoms in 87 early and 73 late onset male alcoholics differ from one another. The authors administered a 19-item alcohol abuse/dependence symptom checklist with items based on the DSM-III criteria. Nine of the 19 symptoms were reported significantly more often in the early than in the late onset alcoholics. Antisocial behaviors were reported to have been particularly frequent in the early onset group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Battered women have a higher prevalence of anxiety disorders compared to the general female population (Foa et al, 2000). Battered women are also at risk for substance abuse (Watson et al, 1997). In the Swan and Snow (2003) study, 24% of the women met criteria for problem drinking.…”
Section: Discussionmentioning
confidence: 94%
“…Battered women have a higher prevalence of anxiety disorders compared to the general female population (Foa et al, 2000). Battered women are also at risk for substance abuse (Watson et al, 1997). In the Swan and Snow (2003) study, 24% of the women met criteria for problem drinking.…”
Section: Discussionmentioning
confidence: 94%
“…The cutoff age of 13 for early-onset alcohol consumption is based on previous literature about preteen initiation of drinking (e.g., see Dube et al, 2006;Hamburger et al, 2008). The cutoff age for early-onset socially maladaptive drinking and early alcohol-dependence clinical features is 23 years old, based on previous literature and a sample-specifi c consideration of how many cases would be needed to ensure suffi cient statistical precision in estimation of the CPP-AUD association before stratifi ed analyses were undertaken, as described below (Brown and Anderson, 1991;Moss et al, 2008;Watson et al, 1997).…”
Section: Response Variables: the Drinking-related Outcomes Of Interestmentioning
confidence: 99%
“…One subgroup among older adults with AUD and heavy use are those individuals who have experienced onset of alcohol problems after the age of 50 (late-onset) (see Atkinson et al, 1990;Watson et al, 1997). In a small correlational study with 60 participants, Adams and Waskel (1991b) found that as many as 11% (n = 7 of 60) of all older adults with AUD had experienced a late onset (50+) of their problem.…”
mentioning
confidence: 99%
“…More often than early-onset AUD, later onset abusers seem to be referred to treatment by court order (i.e., for drink driving; Atkinson et al, 1990). According to Watson et al (1997) and Christopherson, Escher, and Bainton (1984), late-onset AUD seems to be associated with fewer socially unacceptable symptoms than does early-onset AUD. Wetterling et al (2003) found that individuals with late-onset AUD are less frequently diagnosed as dependent on alcohol.…”
mentioning
confidence: 99%